1992
DOI: 10.1080/01635589209514185
|View full text |Cite
|
Sign up to set email alerts
|

Dietary micronutrients and cervical dysplasia in southwestern American Indian women

Abstract: American Indian women in the Southwest have high rates of cervical cancer and cervical dysplasia in contrast to low rates of cancers for other sites. Despite their high rates of cervical disease, no published information has specifically examined risk factors for cervical cancer or cervical dysplasia among American Indian women. We carried out a pilot case-control study of cervical dysplasia in southwestern American Indian women to examine the relationship of dietary intake of vitamin C, folacin, vitamin E, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Although case-control studies suggested an inverse association between vitamin E intake and invasive cervical cancer, 18,31,32 inconsistent results have been reported for noninvasive lesions. 30,[33][34][35][36][37] Two prospective studies suggest a protective effect of dietary beta-carotene 15,16 against HPV persistence, but results from case-control studies on ISC are inconsistent, 22,26,31,38 and a meta-analysis of RCT 7 did not observe a beneficial effect. Folate intake on ISC has been assessed in some case-control studies 26,39 and results were also inconsistent, and a meta-analysis of RCT 7 did not observe an effect.…”
Section: Discussionmentioning
confidence: 99%
“…Although case-control studies suggested an inverse association between vitamin E intake and invasive cervical cancer, 18,31,32 inconsistent results have been reported for noninvasive lesions. 30,[33][34][35][36][37] Two prospective studies suggest a protective effect of dietary beta-carotene 15,16 against HPV persistence, but results from case-control studies on ISC are inconsistent, 22,26,31,38 and a meta-analysis of RCT 7 did not observe a beneficial effect. Folate intake on ISC has been assessed in some case-control studies 26,39 and results were also inconsistent, and a meta-analysis of RCT 7 did not observe an effect.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study provide evidence that inadequate reserve of folate, as reflected in RBC folate contents may enhance the effect of tobacco smoking on OED risk. Furthermore, low level of folate was found to be related to an increased risk of epithelial dysplasia or carcinoma-in-situ [44,45]. These nutrients are likely to take the active role in the risk reduction effect.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a case-control study that assessed dietary intake of nutrients and vitamins among AI women living in the Southwest concluded that low intake of vitamin C, folate, and vitamin E increased the risk of cervical dysplasia. [22]…”
Section: Discussionmentioning
confidence: 99%